POLA PRODUKSI BIOLISTRIK Aneurinibacillus thermoaerophilus STRAIN N25 PADA VARIASI SUBSTRAT LIMBAH PERTANIAN - Dinda Aulia Nabila; Irdawati; Dezi Handayani; Elsa Yuniarti (Jurnal Biogenerasi, 2026)
The increasing energy demand encourages the development of renewable energy technologies such as Microbial Fuel Cell (MFC), which converts organic substrates into electricity using microorganisms. This study aimed to analyze bioelectricity production by Aneurinibacillus thermoaerophilus strain N25 using different substrates (glucose, corn cob, rice straw, and rice husk). The experiment was conducted using a dual-chamber MFC system with voltage measurements over 24 hours. The results showed that voltage increased over time, peaked at the 20th hour, and then decreased. The highest voltage was produced by glucose (0.802 mV), followed by corn cob (0.724 mV), rice straw (0.581 mV), and rice husk (0.491 mV). These results indicate that substrate type affects bioelectricity production, with corn cob as the best agricultural waste substrate.